MODEL WORK-LIFE BALANCE DALAM PENINGKATAN EMPLOYEE ENGAGEMENT PADA PEREMPUAN BEKERJA YANG MENJALANI PERAN GANDA - Sulis Mariyanti; Lita Patricia Lunanta; Aisyah Ratnaningtyas (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2022)
Women who have multiple roles hope to live a balanced life. On the one hand, as an employee, she tries to be engaged in her work to a maximum performance. On the other hand, personal matters, household domestic tasks can be completed satisfactorily to make them happy. One of the efforts that can be made by women who have multiple roles to remain engaged in their work is to balance their personal affairs with their work or work-life balance. The purpose of this study was to determine the effect of work-family balance on the work engagement of working women who have multiple roles. This research method is quantitative-causal comparative with a purposive sampling technique, involving 201 working and married mothers in Indonesia. The work-life balance measurement tool refers to the theory of Greenhaus et.al (2002) with 21 valid items (range (r) ≥ 0.3) and reliability (α) = 0.905. The work engagement scale uses the Utrecht Employee Engagement Scale (UWES) from Schaufeli and Bakker (UWES) adapted from Titien (2016) with 28 valid items and reliability (α) = 0.922. The results of this study indicate that there is an effect of work-life balance on work engagement in working women who have multiple roles with a significant value (p) of 0.000 (p <0.05), with a simple linear regression equation Y = 1.138 + 0.614 X1. Work-Life Balance contributes 51.5% to Employee Engagement. More working women who have multiple roles feel a low work life balance (62.7%) and also more have low work engagement (61.7%). Keywords: Work-life balance, work engagement, women, work, multiple roles, Indonesia Perempuan yang menjalani peran ganda berharap dapat menjalani kehidupannya dengan seimbang. Di satu sisi, sebagai karyawati, ia berupaya bisa engaged terhadap pekerjaannya hingga berkinerja maksimal. Di sisi lain urusan pribadi, tugas domestik rumah tangga pun dapat diselesaikan dengan memuaskan hingga membuatnya bahagia. Salah satu upaya yang dapat dilakukan oleh perempuan yang menjalani peran ganda agar tetap engaged terhadap pekerjaannya adalah dengan tetap menyeimbangkan urusan pribadinya dengan pekerjaannya atau work-life balance. Tujuan penelitian ini untuk mengetahui pengaruh work-family balance terhadap work engagement perempuan bekerja yang menjalani peran ganda. Metode penelitian ini berjenis kuantitatif-kausal komparatif dengan teknik purposive sampling, melibatkan 201 ibu bekerja dan telah menikah di wilayah Indonesia. Alat ukur work-life balance mengacu pada teori Greenhaus et.al (2002) dengan 21 item valid (rentang (r) ≥ 0,3) dan reliabilitas (α) = 0,905. Skala work engagement menggunakan Utrecht Employee engagement Scale (UWES) dari Schaufeli dan Bakker (UWES) yang diadaptasi dari Titien (2016) dengan 28 item valid dan reliabilitas (α) = 0,922. Hasil penelitian ini menunjukkan ada pengaruh work-life balance terhadap work engagement pada perempuan bekerja yang menjalani peran ganda dengan nilai signifikan (p) sebesar 0,000 (p < 0,05), dengan persamaan regresi linier sederhana Y= 1,138 + 0,614 X1. Work-Life Balance berkontribusi 51,5% terhadap Employee Engagement. Perempuan bekerja yang menjalani peran ganda lebih banyak yang merasakan work life balance rendah (62,7%) dan juga lebih banyak yang memiliki work engagement rendah (61,7 %) Kata Kunci: Work-life balance, work engagement, perempuan, bekerja, peran ganda, Indonesia